Da instrumentalização para o trabalho à potencialização da existência: uma etnodesenhografia da expressão subjetiva contemporânea - Pereira, Carla Freitas Pacheco (2022)
This research consists of an investigation into the forms of human subjectivation, taking as a starting point the graphic expression and the use of drawing as a language in Brazilian Architecture and Urbanism courses. The problem concerns the possibility of changing the traditional models of teaching drawing, issues of instrumentalization for work and the prospects of potentialization of life. The question that arises is that of the current model of teaching drawing, a tributary of the computational mediation that resides in annulling the temporal experience, full and dense time. In contrast, drawing be understood as an experience of singular expression capable of producing affection in the working body of the designer, which, therefore, is opposed to drawing methods by computer-assisted models. The graphic expression as a body's knowledge becomes a possibility to act in the production of life. This knowledge makes it possible to activate and reactivate ways of being in the world, thus mediating insurgencies by operating fissures and reconfiguring the field of human experience. The drawing experiences carried out by groups of urban sketchers operate a reconquest of time, a path of inhabiting it while sustaining a body-soul. Draw with the whole body presented as the beginning of an insurgent process. Thus, the research work articulates areas of knowledge concerning the investigation of subjectivity, like Philosophy and Psychology, with those that investigate the expression of landscape through Architecture and Urbanism. The field investigation had based on two expeditions to events of urban sketchers using the ethnographic method of prolonged observation of situations and people. The urban sketcher groups are experiences of exchanging knowledge that operate on the edges of the traditional model of teaching drawing. The ethnographic observation pointed to two categories of analysis, and then cartography traced the processes of experimentation carried out within the scope of these ethnographic journeys. And so, drawing has been intended as an aesthetic, ethical and political expression of the creative insurgent. This way of thinking constitutes an emancipated subjectivity. The thesis that develops from these studies is that appropriating drawing as a bodily experience increases the intensity of the perception of the concrete forms of the world. It is an outlook theoretical and practical for drawing teaching. There is a transmutation of teaching practices into an affection event, not merely an intellectual one. And finally, shift from instrumentalization to work towards the potentialization of existence.